P73 LEARN: uroLogical tEAching in bRitish medical schools Nationally - a national retrospective multi-centre audit of urology teaching across British medical schools. (8th April 2021) - Ng, A; Cambridge, W A; Jayaraajan, K; Lam, C M; Light, A; Asif, A; Chan, V W S; Matthews, M G; Clement, K; Kulkarni, M; Bhatt, N R; Khadhouri, S; et al.
Abstract: Introduction: Urological conditions account for approximately 25% of acute surgical referrals and 10-15% of general practitioner appointments. In 2012, the British Association of Urological Surgeons (BAUS) produced 'An Undergraduate Syllabus for Urology', advising on common clinical areas of urology that must be covered during undergraduate medical training. However, its uptake nationally remains unknown. This project aims to assess undergraduate urology teaching across UK medical schools. Methods: A targeted advertising drive using social media, medical school societies, websites and newsletters was performed over 4 weeks. Collaborators are responsible for recruiting survey respondents (year 2 medical students to foundation year 1 (FY1) doctors). Survey respondents will complete a REDCap survey retrospectively assessing their urology teaching to date. The primary objective is to compare current urology teaching in medical schools across the United Kingdom with the BAUS undergraduate syllabus. Results: Currently, 522 collaborators have registered from 36 medical schools nationally. Of these collaborators, 6.32% (33/522) are FY1s and 93.68% (489/522) are medical students. Each collaborator will be responsible for recruiting at least 15 survey respondents to be eligible for PubMed-indexed collaborator authorship. Conclusion: LEARN has recruited successfully to date, with all collaborators from the medical student and FY1 cohort. With the role of collaborators to further recruit survey respondents, LEARN will provide the most representative and thorough evaluation of UK undergraduate urological teaching to date. It will provide evidence to support changes in the medical school curriculum, and allow re-evaluation of the current national undergraduate BAUS syllabus.